Persepsi masyarakat India terhadap agama dan komuniti Islam Taman Kajang Utama dan Taman West Country - Ahmad Redzuwan Mohd Yunus,; Badlihisham Mohd Nasir, (Penerbit Universiti Kebangsaan Malaysia, 2003)
The objective of the research is to study the perception of the Indian community towards Islam and its nation in Taman Kajang Utama and Taman West Country, Kajang. It is also aimed to examine their perception towards Islamic activies promoted by the local Muslim community. In order to achieve the objective of the study, the research have employed two common methodologies namely library and fieldwork approaches. The finding of the study is that the Indian community has a positive perception towards the religion of Islam. Nevertheless, their perception towards Muslim and the Islamic activities is considerably less supportive if not negative